Exploring the Role of Mindfulness in Promoting Academic Resilience Among Disadvantaged Learners - Putra, Ivandro Arsena; Huwae, Arthur (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Suburban high school students often face considerable academic challenges due to limited school infrastructure, inadequate facilities, and a lack of educational support—conditions that can undermine academic development and resilience. While prior studies have explored the link between mindfulness and academic resilience, few have specifically examined this relationship within structurally disadvantaged school settings. This study addresses this gap by investigating the correlation between mindfulness and academic resilience among students in suburban high schools in Indonesia. Employing a quantitative correlational design, the study surveyed 535 students from four suburban schools in Semarang Regency, using the Five Facet Mindfulness Questionnaire (α = .914) and the Academic Resilience Scale (ARS-30) (α = .958). Spearman’s Rho analysis revealed a weak yet statistically significant positive correlation (r = .162, p < .001), with the non-reactivity facet of mindfulness showing the strongest association with resilience. Despite the small effect size (R² = .036), the findings offer novel insights into how mindfulness may serve as a psychological buffer for students navigating under-resourced academic environments. The results underscore the importance of contextually tailored mindfulness-based interventions and call for further research into additional factors that influence resilience in disadvantaged educational settings. This study contributes new evidence to the field by situating mindfulness within the lived realities of suburban learners and advancing the understanding of resilience in marginalized school populations.